Pengaruh Budaya Organisasi, Gaya Kepemimpinan Transformasional dan Komitmen Organisasi Terhadap Kinerja Karyawan Dengan OCB Sebagai Variabel Intervening - Imam Baihaqi; Saifudin S (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the influence of Organizational Culture, Transformational Leadership Style and Organizational Commitment on Employee Performance with Organizational Citizenship Behavior as an Intervening variable on employees of BSI KC Semarang. The sample used in this study were 44 respondents with the sampling technique saturated sampling technique. The method of collecting data is by giving a questionnaire. The analysis technique in this research includes regretion analysis, statistical test, classical assumption test and path analysis. Furthermore, processing the data that has been obtained is processed with SPSS tools. Based on the results explains that: 1) organizational culture has a positive and significant effect on employee performance, 2) transformational leadership style has no effect on employee performance, 3) organizational commitment has no effect on employee performance, 4) OCB has a positive effect and significant on employee performance, 5) organizational culture has no effect on ocb, 6) transformational leadership style has no effect on OCB, 7) organizational commitment has a positive and significant effect on OCB, 8) ocb does not mediate the effect organizational culture on employee performance, 9) OCB does not mediate the effect of transformational leadership style on employee performance, 10) OCB is able to mediate the influence of commitment or ganization of employee performance.